THE CONDITION OF DISTAL AORTA AFTER PROXIMAL RECONSTRUCTION FOR DISSECTION IN MARFAN SYNDROME - A. M. Chernyavskiy; M. M. Lyashenko; D. A. Sirota; S. A. Alsov; D. S. Khvan (Российский кардиологический журнал, 2016)
Marfan syndrome is a disease associated with high prevalence of aorta-related morbidity and mortality. Dissections and ruptures of thoracal aorta (ThAo) lead to decreased life duration in persons with Marfan syndrome with mediana at 30 year-old.Aim. To study the changes of distal aorta and clinical outcomes after surgical treatment for proximal aorta dissection in Marfan syndrome.Material and methods. In the SRICP, among patients operated for proximal aorta dissection, 14 were selected, who had histologically proven Marfan syndrome. They were followed-up.Results. In the long-term follow-up after the intervention on thoracoabdominal aorta (TAAo) was required in 2 patients. Reasons for transforming of the distal aorta were the age of the disease onset (p=0,04), acute stage of dissection (p=0,02). Changes in TAAo developed during first months after primary intervention, as inseveral years.Conclusion. Surgery for proximal dissections in Marfan syndrome patients is related to acceptable levels of morbidity and mortality in early and post-operation periods. Regular follow-up is required of such patients in post-operation period for on-time diagnostics and performing of secondary interventions.